2020
DOI: 10.1111/1755-6724.14601
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Evolution of Pre‐Neoproterozoic Continental Crust in South China: A Review and Tectonic Implications

Abstract: South China as an amalgamation of the Yangtze and Cathaysia blocks is composed of Archean to Mesoproterozoic basement overlain by Neoproterozoic and younger cover. Both the constituent Yangtze and Cathaysia blocks contain well‐preserved Neoproterozoic rocks that have been extensively studied in terms of the age and tectonic nature, but less is known about their earlier crustal history due to the incomplete rock record. Recent efforts in investigating the yet survived crustal nature based on isotopic and elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 151 publications
1
12
0
Order By: Relevance
“…Neoarchean grains account for about 20% of the CTAC detrital zircons and have an age peak at ~2.7 Ga (Figure 8). Widespread 2.8–2.6 Ga detrital, inherited, and xenocrystal zircons indicate that tectonothermal events occurred extensively in the Yangtze Block during the Neoarchean era (Wang et al, 2020; Wang, Dong, Yao, & Zhao, 2020; Xiang et al, 2018; Zheng et al, 2006), representing a significant period for crustal growth and reworking similar to many other major Archean cratons worldwide (Condie et al, 2009). This view has been further supported by a growing number of Neoarchean magmatic rocks that have been recently identified within the Kongling (Chen, Gao, et al, 2013; Gao et al, 2011; Guo et al, 2015), Zhongxiang (Huang et al, 2020; Wang, Deng, et al, 2018; Wang, Li, et al, 2018; Zhou et al, 2015), Yudongzi (Chen et al, 2019; Hui et al, 2017; Zhou et al, 2018), and Phan Si Pan (Zhao et al, 2019) complexes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Neoarchean grains account for about 20% of the CTAC detrital zircons and have an age peak at ~2.7 Ga (Figure 8). Widespread 2.8–2.6 Ga detrital, inherited, and xenocrystal zircons indicate that tectonothermal events occurred extensively in the Yangtze Block during the Neoarchean era (Wang et al, 2020; Wang, Dong, Yao, & Zhao, 2020; Xiang et al, 2018; Zheng et al, 2006), representing a significant period for crustal growth and reworking similar to many other major Archean cratons worldwide (Condie et al, 2009). This view has been further supported by a growing number of Neoarchean magmatic rocks that have been recently identified within the Kongling (Chen, Gao, et al, 2013; Gao et al, 2011; Guo et al, 2015), Zhongxiang (Huang et al, 2020; Wang, Deng, et al, 2018; Wang, Li, et al, 2018; Zhou et al, 2015), Yudongzi (Chen et al, 2019; Hui et al, 2017; Zhou et al, 2018), and Phan Si Pan (Zhao et al, 2019) complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that collision‐related magmatism and metamorphism may have been dominant in the Yangtze Block at 2.0–1.8 Ga (e.g., Cui et al, 2020; Cui, Wang, et al, 2021; Han et al, 2019; Huang et al, 2019; Hui et al, 2017; Wang & Dong, 2019; Wang et al, 2015, 2016; Wu et al, 2008; Yin, Lin, Davis, Zhao, et al, 2013; Zhao et al, 2019; Zhou et al, 2017). These observations lead to a consensus that one significant episode of craton‐scale orogeny may have occurred in the Yangtze Block during 2.0–1.8 Ga (Cawood et al, 2018, 2020; Cui, Wang, et al, 2021; Han et al, 2019; Wang & Dong, 2019; Wang, Dong, Yao, & Zhao, 2020), synchronous with the global orogenic events that resulted in the amalgamation of Nuna supercontinent (Zhao et al, 2002) (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is located in eastern Europe, and western, southern, eastern, and southeastern Asia (Figs. 1 and 2), surrounded by the Arabia, India, North China, Tarim, and East Europe cratons, with the South China block, i.e., the Yangtze craton and the Cathaysia block (Wang K et al, 2020), and the Indosinian craton involved in. It is mainly composed of the Alps, Zagros, Hindu Kush, Himalaya, and Qinling-Dabie mountains, and the Iranian, Pamir, and Qinghai-Tibetan plateaus, extending more than 15000 km from east to west.…”
Section: The Tethys Regimementioning
confidence: 99%